Julie Mostov. Soft Borders: Rethinking Sovereignty and Democracy - (USA), Maria Hnaraki (Гласник Етнографског института САНУ; Издање 57 Број 2 (2009), 2009)
Julie Mostov. Soft Borders: Rethinking Sovereignty and Democracy Palgrave Macmillan, May 2008 A political theorist who has lived, studied and worked in former Yugoslavia since the 1970s, conceptualizes political space and relationships of social cooperation. Soft Borders encourages sustainable resolutions to ethno-national conflicts, economic and social development.